IMPLEMENTASI KURIKULUM MUATAN LOKAL PENDIDIKAN DINIYAH DALAM PENINGKATAN NILAI SOSIAL DAN SPIRITUAL DI SMPN 1 PETERONGAN - Rochmad Basuni; Imam Bawani (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article aims to describe and analyze the implementation of the local content curriculum of diniyah education in improving the social and spiritual values of students at SMPN 1 Peterongan. This study used a qualitative approach with a case study method. Data collection techniques were carried out through observation, in-depth interviews with the principal, Islamic education teachers, and students, as well as curriculum documentation. Data analysis used data reduction, data presentation, and conclusion drawing. The results of the study show that the local content curriculum for diniyah education is structured through activities such as learning basic texts, daily worship practices, and character training. In its implementation, diniyah education is able to shape social attitudes such as cooperation, responsibility, and tolerance among students.  From a spiritual perspective, students showed improvement in religious discipline, understanding of religious values, and personal integrity. The main factors supporting the success of this implementation were the commitment of school management, teacher competence, and active student involvement. However, several obstacles were also identified, such as limited implementation time and a lack of contextual teaching resources. This study concludes that the implementation of the local content curriculum for diniyah education has a positive influence in shaping the overall social and spiritual character of students. The researchers recommend strengthening the synergy between schools, teachers, and parents for the sustainability of the diniyah program as an integral part of character education in public schools.